Urinary neutrophil gelatinase-associated lipocalin: a marker of urinary tract infection among febrile children - Ji Hyun Moon; Kee Hwan Yoo; Hyung Eun Yim (The Korean Pediatric Society, 2021)
Background Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as a valuable biomarker of urinary tract infection (UTI) in children. Purpose This study aimed to compare the diagnostic accuracy of urinary NGAL (uNGAL) with those of serum C-reactive protein (CRP) and white blood cell (WBC) count for predicting UTI and acute pyelonephritis (APN) in febrile children. Methods The medical charts of children undergoing uNGAL measurements between November 2017 and August 2019 were retrospectively reviewed. Patients with a suspected or diagnosed UTIs were included. The diagnostic accuracies of uNGAL, serum CRP, and WBC count for detecting UTI and APN were investigated. Independent predictors of UTI and APN were investigated using multivariable logistic regression analyses. Results A total of 321 children were enrolled in this study. The uNGAL levels were higher in the UTI group (n=157) than in the non-UTI group (n=164) (P<0.05). Among children with a UTI, uNGAL levels were higher in the APN group (n=70) than, the non-APN group (n=87) (P<0.05). In the multivariate analysis, uNGAL was independently associated with UTI and APN (both P<0.05). Serum CRP and WBC count were not correlated with the presence of UTI and APN. Receiver operating curve analyses showed that the uNGAL level had the highest area under the curve (AUC) for predicting UTI and APN, respectively (AUC, uNGAL vs. CRP vs. WBC count, 0.860 vs. 0.608 vs. 0.669 for UTI; 0.780 vs. 0.680 vs. 0.639 for APN, all P<0.05, respectively). The predictive values and likelihood ratios of uNGAL were superior to those of serum CRP and WBC count for detecting UTI and APN at each cutoff level. Conclusion UNGAL may be more useful than serum CRP and WBC count for identifying and assessing UTI in febrile children.